Distribution Patterns of Latex Sucrose Content and Concurrent Metabolic Activity at the Trunk Level with Different Tapping Systems and in Latex Production Bark of Hevea brasiliensis - Pisamai Chantuma; Sornprach Thanisawanyangkura; Poonpipope Kasemsap; Eric Gohet; Phillipe Thaler (Agriculture and Natural Resources, 2006)
Distribution patterns of latex sucrose content and concurrent metabolic activity at the trunk level with different tapping systems, namely 1/2S d/2 (a half spiral cut alternate daily), 1/2S d/3 ET 2.5%.8/y (a half spiral cut one day in tapping followed by two days of rest, stimulated with ethephon, eight applications per year) and DCA (Double Cut Alternate, 2×1/2S d/4 (t,t), two half spiral cuts, each cut tapped alternate on every four days) were studied. RRIM600 rubber trees were used to map the latex metabolic status from different heights on both panel A and panel B. Latex was collected by puncturing trunks at various positions and was analyzed using Latex Diagnosis technique (LD). The concurrent comparison of latex sucrose and inorganic phosphorus concentrations for every sampling position allowed estimating the size and shape of the actual latex regeneration area. Regular tapping induced latex sucrose depletion in tapped panel bark. This sucrose depletion was enhanced by the use of DCA, as a consequence of increased production and therefore higher latex regeneration metabolism. DCA also induced a huge sucrose sink effect above tapped cut on both panel A and panel B and outside the metabolically active area.